Performance Assessment of a nZEB Carbon Neutral Living/Office Space and Its Integration into a District Energy-Hub - Pietro Florio; Xavier Tendon; Jérémy Fleury; Carlotta Costantini; Andreas Schueler; Jean-Louis Scartezzini (Energies, 2022)
The integrated performance assessment of buildings can orient their design in the early stages. Despite the wide availability of physics simulation-based, data-driven, and hybrid techniques, it is often difficult to rely on a single, appropriate technique to obtain reliable results. A set of methods, each featuring advantages and limitations, help to refine the performance assessment in an iterative comparative process until a comprehensive picture of the building is achieved. The approach was implemented on a nearly zero-energy building, recently built-up as a combined living and office space (e.g., the SolAce unit) on the NEST infrastructure in Dübendorf (Switzerland). The proposed approach showed that the unit reaches high energy performance accordingly requiring optimal cooling management, involving the control of the opening of blinds and windows. A sound convergence between the computer simulations and data-driven analysis were observed, attesting to the overall energy consumption, of around 26 kWh/m2year, in continuous decrease, aiming at an annual energy-positive balance. The unit was ranked first according to the dynamic energy exchange scheme of the energy trading hub within the NEST facility, which features high-level building modules as a testbed of future building technologies. Embodied energy is estimated at 39 kWh/m2year, which is below the commended limits of Swiss eco-building standards. By considering the carbon sequestration of the wood products during their lifespan, the unit is very close to carbon neutrality with the CO2 emitted annually by the unit over its lifetime being compensated by those stored within wood products during the same period. Highlights: An innovative combined living/office space is connected to an ‘Energy-hub’. The unit includes novel bioclimatic developments of the building industry. Energy performance is assessed in the concept phase, construction, and operation. Used and compared simulation vs data monitoring for energy and comfort assessment. High energy performance and neutral CO2 emission; plus-energy exported to the hub.